The Beauty of Qur’anic Rhetoric: A Synaesthetic Metaphor Analysis in Surah Al-Waqi’ah - Farhatul Maulidya; Rifqatul Husna (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The Qur’an not only conveys normative teachings but also presents an aesthetic linguistic dimension that functions to construct readers’ spiritual experience. One of the key aspects in Qur’anic stylistic studies is synaesthetic metaphor, namely the transfer of sensory perception across different senses used to concretize abstract concepts. This study aims to identify the forms of synaesthetic metaphors in Surah Al-Waqi’ah and to analyze their rhetorical functions in constructing readers’ visual, emotional, and spiritual experiences. This research employs a qualitative approach using a library research method. Primary data are derived from the text of Surah Al-Waqi’ah, while secondary data are obtained from relevant literature in tafsir, Arabic rhetoric (balaghah), stylistics, and previous studies. Data analysis is conducted through identification, classification, and interpretation of linguistic meaning. The findings indicate that synaesthetic metaphors in Surah Al-Waqi’ah operate through sensory transfers involving sight, touch, and taste, thereby transforming eschatological concepts into more concrete experiential representations. Rhetorically, these metaphors enhance imaginative power, intensify emotional response, and strengthen spiritual awareness. Thus, synaesthetic metaphor functions not only as an aesthetic linguistic device but also as a communicative instrument in conveying the theological messages of the Qur’an.